2007
DOI: 10.1364/josaa.24.002817
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-noise ratio trade-offs associated with coarsely sampled Fourier transform spectroscopy

Abstract: We derive the spectral signal-to-noise ratio (SNR) trade-offs associated with coarsely sampled Fourier transform spectroscopy using a step-and-integrate measurement scheme. We show that there is no SNR penalty in the shot noise limit and a slight SNR benefit in the detector noise limit for the case of coarse sampling to achieve the same spectral resolution as a baseline Nyquist sampling scenario, where the total detector integration time is the same for both sampling cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…5 (A). This observation is in line with the theoretical simulations presented by Thurman and Fienup [33]. Figure 5(B) shows de-noised recovery of the same spectrum using TwIST along with sparsity priors.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…5 (A). This observation is in line with the theoretical simulations presented by Thurman and Fienup [33]. Figure 5(B) shows de-noised recovery of the same spectrum using TwIST along with sparsity priors.…”
Section: Resultssupporting
confidence: 88%
“…To validate this point, we have demonstrated full-field Raman imaging using the proposed design. We also experimentally demonstrated that under-sampled interferogram acquisition can speed up Raman imaging by an order of magnitude at an expense of SNR as proven theoretically in [33]. However, we further demonstrated that low SNR Raman spectra can be de-noised using sparsity priors.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…5. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; and h•i is the ensemble average, equivalent to the time average from start time t a to end time t b defined by…”
Section: Measurement Model a Source To Beam Combinermentioning
confidence: 99%
“…Conversely, the range of recovered wavenumbers is κ max because only positive values of κ are physical. In fact, due to system transmissivity and detector limitations, the interferometer's bandpass is less than κ max , suggesting 0 < κ min < κ max ; knowledge of the bandpass can be exploited, provided the measurements have an adequate signal-to-noise ratio, thus allowing the delay line sampling to be relaxed as for FTIS [12].…”
Section: Measurement Set and Samplingmentioning
confidence: 99%